Study of the Ternary Mixture of Methanol/Formamide/Acetonitrile via Solvatochromic Probes - Nelson Nunes; Ruben Elvas-Leitão; Filomena Martins (Molecules, 2024)
Following previous studies, the ternary mixture of methanol/formamide/acetonitrile (MeOH/Formamide/MeCN) was studied using the UV-Vis absorption spectra at 298.15 K with a set of five probes, 4-nitroaniline, 4-nitroanisole, 4-nitrophenol, N,N-dimethyl-4-nitroaniline and 2,6-diphenyl-4-(2,4,6-triphenyl-1-pyridinio)phenolate (Reichardt betaine dye), for a total of 22 mole ternary fractions. In addition, nine mole fractions of the underling binary mixtures, MeOH/Formamide and Formamide/MeCN were also tested. Spectroscopic results were used to model the preferential solvation order for each probe in the mixtures. The Kamlet–Taft solvatochromic solvent parameters, α, β, and π*, were also computed through the use of the solvatochromic shifts of the five probe indicators. Moreover, discrepancies in the spectroscopic behavior of 4-nitrophenol in formamide-rich mixtures were observed and analyzed.